1977
DOI: 10.1136/jcp.30.5.481
|View full text |Cite
|
Sign up to set email alerts
|

Apparent hypoxic changes in pulmonary arterioles and small arteries in infancy.

Abstract: Some signs indicating a terminal hypoxic episode have been found in cases of the sudden infant death syndrome (SIDS). These include intrathoracic petechial haemorrhages in the lungs, heart, and thymus. Nevertheless the actual cause of such a hypoxic episode is still speculative. One of the current theories concerning the aetiology of the SIDS is that of Steinschneider (1974). He has suggested that in many cases of sudden infant death there are episodes of prolonged sleep apnoea and while such episodes may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
8
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
3
8
0
Order By: Relevance
“…The evidenee that chronic mild hypoxia preceded death of SIDS is based on detailed studies of tissues obtained at autopsy. Naeye (1973) reported that approximately 60 percent of the SIDS infants exhibited medial museie hypertrophy of the pulmonary arterioles, a finding eonfinned by Wi/liams et al (1979), but not found by Kendeel and Ferris (1977). A similar pereentage had an increase in the weight of the right ventriele, persistent extra medullary hematopoesis in the liver and retention of brown fat (Naeye 1980 Fetal and neonatal heart rates in subsequent siblings and controls.…”
Section: Study Resultsmentioning
confidence: 95%
“…The evidenee that chronic mild hypoxia preceded death of SIDS is based on detailed studies of tissues obtained at autopsy. Naeye (1973) reported that approximately 60 percent of the SIDS infants exhibited medial museie hypertrophy of the pulmonary arterioles, a finding eonfinned by Wi/liams et al (1979), but not found by Kendeel and Ferris (1977). A similar pereentage had an increase in the weight of the right ventriele, persistent extra medullary hematopoesis in the liver and retention of brown fat (Naeye 1980 Fetal and neonatal heart rates in subsequent siblings and controls.…”
Section: Study Resultsmentioning
confidence: 95%
“…In our study, the relative medial thickness of the alveolar wall arteries did not significantly differ between SIDS cases and age-matched controls, confirming our previous finding [ 15 ]. The conflicting results of other studies [ 8 , 9 , 12 , 14 ] are likely a result of differing analytical methods and the lack of standardized SIDS definitions, case investigations, and autopsies. Given hypoxia-induced smooth muscle proliferation in pulmonary arteries requires several days, the duration and/or severity of hypoxic exposure relative to the time of death must also be considered.…”
Section: Discussionmentioning
confidence: 98%
“…These changes suggested the presence of chronic hypoxemia in infants with SIDS and refuted the concept that death was a result of a single asphyxiating episode. Naeye's results were challenged by Kendeel and Ferris, 9 who failed to find similarities between infants with SIDS and infants who lived at high altitudes. Naeye's results were expanded and supported by Williams and associates, 10 who found extension of muscle in the pulmonary arterioles toward the periphery of the bronchioles in victims of SIDS.…”
mentioning
confidence: 98%